ANALISIS KESULITAN MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR DALAM MENYELESAIKAN TUGAS AKHIR PADA MASA PANDEMI COVID-19 - Arsita, Mesi; Antosa, Zariul; Noviana, Eddy (Jurnal Ilmiah Aquinas, 2022)
This study aims to describe the difficulties experienced by elementary school teacher education students in completing their final assignments during the covid-19 pandemic. This research uses descriptive quantitative method. The data collection technique used in this study used a questionnaire or questionnaire distributed to 78 respondents. The data analysis technique used was descriptive statistical data analysis techniques. Sources of data in this study are primary and secondary data. The results of this study are that elementary school teacher education students have high enough motivation because they do not want to be a student any longer, students have difficulty in pouring research results into scientific work, students have difficulty identifying educational problems during the covid-19 pandemic. Due to the limited scope, students have difficulty finding references or literature due to the closure of the library so that students use online references which are sometimes difficult to access due to frequent link errors and limited internet quota, and students have difficulty collecting data in the field due to the Physical Distancing policy.